تصميم الاختبار الإلكتروني لترجمة النصوص العربية بالتطبيق على طلبة المدرسة الفرقان المتوسطة بجبمر - Miftahus Sa’diyah; Faishol Nasar bin Madi; Maskud Maskud; Lilis Fauziah (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2023)
It is known that translation is a branch of several disciplines, such as linguistics. Translation is the process of expressing the meaning it conveys in the source language to the target language at a time when that meaning exists in the source language. There is a translation process in learning qiroah in Junior High School Al-Furqan Jember, but students usually cheat during the Arabic exam by copying the answers between students. On the other hand, the evaluation applied is still traditional, that is, using paper or stationery. Therefore, the authors want to develop the exam into an electronic exam. The problem in this study is the design of electronic exams for Arabic text translation in junior high school students Al-Furqan Jember. The research method used by the researcher is ADDIE's RND (research and Development), and this model includes five steps: analysis, design, Development, implementation, and evaluation. Researchers used data collection methods: interviews, observations, documentation, and questionnaires. This study has two types of data analysis: qualitative data and quantitative data. The results in this study: the design of electronic exam for Arabic text translation in Junior High School students Al-Furqan Jember effective to teach the material to translate Arabic text in junior high school students Al-Furqan Jember.